Limits to the power of the State in the face of social protest in Colombia - Macana, Marco Antonio (DIXI, 2024)
The purpose of the article is to clarify the existence of limits on the power of the State in the context of the use of force during social protest in Colombia. This derives: 1) from the analysis of numerals 4 and 5 of the International Covenant on Civil and Political Rights of the United Nations (UN) of 1966, which provides for the use of force by the State in exceptional situations when the life of the nation whose existence has been officially proclaimed by the States that are part of the Covenant is endangered; 2) of Resolution 02903 of 2017 and Decree 03 of 2021 of the Ministry of the Interior, which incorporate the concept of the public as the material object of the conduct, as well as the sanctioning of violence and the disproportionate use of weapons; and 3) of social protest as a fundamental right that contributes to the construction of democracy. Among the findings, it is relevant that the international normative system allows States to limit and restrict freedoms or rights in pursuit of legitimate ends. However, the power is not unlimited and is subject to certain formal rules based on the principle of proportionality and reasonableness generously developed by jurisprudence and doctrine. It is concluded that the use of force by the State is only appropriate when there is a legitimate objective of counteracting conduct that endangers public order and security.